1970
DOI: 10.1177/004051757004001008
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Microscope Study of Cotton Treated with Inter- and Intracrystalline Swelling Agents

Abstract: Electron micrographs are presented of cotton cellulose treated with aqueous solutions of the inter-and intracrystalline swelling agents, morpholine, piperidine, piperazine, ethylenediamine, and zinc chloride. The concentration of each swelling agent was such as to produce maximum recoverable swelling of cotton cellulose. Physical and fine-structure characteristics of these treated cottons, after complete removal of the swelling agent, revealed that morpholine and piperidine are intercrystalline and piperazine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Also, the morpholine pre-treatment process did not lead to a marked reduction in crystallinity index and the 13% decrease observed in comparison to the starting pulp can be attributed to the impact of mechanical shearing (Eyholzer et al 2010;Taheri and Samyn 2016;Tian et al 2016). This result is broadly consistent with the surface chemistry analysis reported in previous studies where morpholine was shown not to affect the crystallinity index of cellulose but to only act as an inter-crystalline swelling agent (Betrabet et al 1966;Betrabet and Rollins 1970;Lokhande 1978;Lokhande et al 1984). In contrast, the carboxymethylation pre-treatment process, coupled with mechanical shearing, led to a 35% decrease in the crystallinity index of CMCNF compared with the starting cellulose pulp.…”
Section: Effect Of Chemical Pre-treatments and Mechanical Processing supporting
confidence: 91%
See 1 more Smart Citation
“…Also, the morpholine pre-treatment process did not lead to a marked reduction in crystallinity index and the 13% decrease observed in comparison to the starting pulp can be attributed to the impact of mechanical shearing (Eyholzer et al 2010;Taheri and Samyn 2016;Tian et al 2016). This result is broadly consistent with the surface chemistry analysis reported in previous studies where morpholine was shown not to affect the crystallinity index of cellulose but to only act as an inter-crystalline swelling agent (Betrabet et al 1966;Betrabet and Rollins 1970;Lokhande 1978;Lokhande et al 1984). In contrast, the carboxymethylation pre-treatment process, coupled with mechanical shearing, led to a 35% decrease in the crystallinity index of CMCNF compared with the starting cellulose pulp.…”
Section: Effect Of Chemical Pre-treatments and Mechanical Processing supporting
confidence: 91%
“…Betrabet, Lokhande and co-workers investigated the use of aqueous morpholine and other amines as swelling agents for cotton to increase its dye uptake (Betrabet et al 1966;Betrabet and Rollins 1970;Kulkarni and Lokhande 1975;Lokhande 1978;Lokhande et al 1984). They observed that aqueous morpholine can swell cotton cellulose without changing its density, crystallinity index and tensile strength (Betrabet et al 1966;Betrabet and Rollins 1970).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some swelling agents are able to break the interchain H-bonds in the crystalline region of the fiber, which results in the intracrystalline swelling and a lowered orientation, a loss of strength, and an increase in moisture uptake and accessibility. 53 Orientation is an important parameter for the tensile properties of cellulose II fibers in that both the ultimate strength and initial modulus increase with increasing orientation. 54 The tensile properties of untreated lyocell fibers depend on their crystallite orientation factor, whereas the tensile strength of lyocell fibers treated with NaOH depend on their amorphous orientation factor.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…A reduction in strength due to the breakage of hydrogen bonds has been found in regenerated cellulose. , In the intercrystalline region (amorphous parts) of cellulose, the orientation of chain molecules in relation to the fiber axis is irregular, and the density of interchain H-bonds is low; therefore, swelling is limited to this region and does not appreciably change the physical properties of cotton fibers. On the other hand, some swelling agents are able to break the interchain H-bonds in the crystalline region of the fiber, which results in the intracrystalline swelling and a lowered orientation, a loss of strength, and an increase in moisture uptake and accessibility …”
Section: Resultsmentioning
confidence: 99%